Differences in Vitamin D Receptor Levels Between Women With Primary Infertility and Women Without Infertility - Shreshta Dewi; Haviz Yuad; Husna Yetti (Universitas Andalas, 2024)
Introduction: Many studies have been done on vitamin D, but there is still a lack of data regarding Vitamin D receptor (VDR) level and infertility, whereas VDR has a vital role in the action of vitamin D. Objective: To determine the differences in VDR levels between women with primary infertility and women without fertility problems. Method: This is a case-control study on women with and without fertility problems in Padang City, conducted from March 2023–January 2024. Serum VDR levels (ng/ml) were examined using the ELISA method in the Biomedicine Laboratory at Andalas University. Differences in VDR levels were calculated using the independent T-test. Results: There were 60 subjects divided into 30 subjects with infertility and 30 subjects without fertility problems. Subjects with primary infertility had more 31-35 years and >35 years old patients (54.8% and 66.7%), more overweight and obese BMI patients (50% and 83.3%), and had experienced infertility for 1-4 years (73.3%). The mean VDR levels in infertility subjects were lower than in subjects without fertility problems (1.73±0.92ng/ml and 2.35±1.30ng/ml), where this difference was statistically significant (p=0.036). Conclusion: VDR levels influence the incidence of primary infertility.